2020
DOI: 10.15567/mljekarstvo.2020.0102
|View full text |Cite
|
Sign up to set email alerts
|

Antimikrobna učinkovitost ljekovitog bilja i njihov utjecaj na kvalitetu sireva

Abstract: Milk and dairy products are the oldest and most widely consumed nutritious foods worldwide. They are highlighted as a source of high-quality proteins and the most important sources of bioactive peptides. Milk proteins have high nutritive value and remarkable medicinal properties. They are known as potential health-promoting ingredients of functional foods, and the dairy industry has already commercialized many milk proteins and peptide-based products which can be consumed as part of a regular daily diet. Besid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Investigations with hens have shown that the dietary addition of thyme, sage, and rosemary essential oil [10] and essential oil mixture [6] increase hens' production, and increases immunity and eggshell quality, in line with the results obtained by Spasevski et al [11], with the usage of powder form of marigold, paprika, and carrot in hens' diet. Due to the link between dietary lipids and developing coronary heart disease, the lipid composition of table eggs is the primary consumer concern, which is the same regarding dairy products [12]. It has been proven that adequate and well-balanced compound feeds for hens can improve the fatty acid profile of the eggs.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations with hens have shown that the dietary addition of thyme, sage, and rosemary essential oil [10] and essential oil mixture [6] increase hens' production, and increases immunity and eggshell quality, in line with the results obtained by Spasevski et al [11], with the usage of powder form of marigold, paprika, and carrot in hens' diet. Due to the link between dietary lipids and developing coronary heart disease, the lipid composition of table eggs is the primary consumer concern, which is the same regarding dairy products [12]. It has been proven that adequate and well-balanced compound feeds for hens can improve the fatty acid profile of the eggs.…”
Section: Introductionmentioning
confidence: 99%
“…Certain studies reported a decrease in hardness of Mozzarella cheese (Ozsunar, 2010; Smith, 2013). Researchers demonstrated that textural characteristics were determined by microbiological growth activity, loss of moisture, enzymatic activity and salt diffusion during ripening in several cheese types (Fox and Wallace, 1997;Puvača et al, 2020). In a study by Metzger et al (2001), a time-dependent decrease in texture was observed.…”
Section: Textural Properties Of Mozzarella Cheesementioning
confidence: 99%
“…Due to their important bioactive components, Turkish Oregano, peppermint, rosemary and basil, which are medicinal and aromatic plants, have been widely used in research (Koç et al, 2018;Sezen et al, 2018). The addition of plants and their essential oils to cheeses prevents the development of pathogenic and spoiling microorganisms and could have a positive effect on cheese quality (Puvača et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Milk and milk products are considered to be the essential components of a balanced human diet as they have tremendous nutritional values regarding a good proportion of proteins, fats, and important minerals (Vuković et al, 2020;Puvača et al, 2020). According to Puvača et al (2020), significant health benefits of milk and its products are related to the proteins, especially their nutritive value and biological properties. Furthermore, milk is a nutrient-dense food with important nutritional value as it contains a good proportion of calcium, potassium, phosphorus, cholecalciferol, cobalamin, retinol, riboflavin, and proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, milk is a nutrient-dense food with important nutritional value as it contains a good proportion of calcium, potassium, phosphorus, cholecalciferol, cobalamin, retinol, riboflavin, and proteins. Milk is an important source of niacin equivalents as it has a sufficient content of the tryptophan amino acid, a niacin precursor (Puvača et al, 2020). Free of contaminants, liquid milk is an essential alimentative and healthful food for infants and elderly population (Battu et al, 2004).…”
Section: Introductionmentioning
confidence: 99%